Antarctic Sea Ice Expansion, Driven by Internal Variability, in the Presence of Increasing Atmospheric CO2. Issue 24 (24th December 2019) - Singh, H. A.; Polvani, L. M.; Rasch, P. J.
Abstract: A number of physically based hypotheses have been proposed to explain the surprising expansion of Antarctic sea ice area (SIA) over the satellite era (1979 to 2015). Here, we use a fully coupled state‐of‐the‐art global climate model to show that internal variability alone can produce such multidecadal periods of Antarctic SIA expansion even as atmospheric CO2 increases at observed rates and the planet warms. When our model is started from a relatively warm Southern Ocean state, Antarctic SIA sometimes (in one of three ensemble members) expands over multidecadal time scales at a rate comparable to that over the satellite era. SIA expansion occurs concurrently with rising atmospheric CO2 and warming global surface temperatures, and SIA trends by region and sector resemble those over the satellite era. Our results suggest that internal variability over long time scales in the Southern Ocean region may suffice to explain Antarctic SIA expansion over the satellite era. Key Points: Internal variability can drive Antarctic sea ice area expansion, even as atmospheric CO2 rises Such Antarctic sea ice expansion can occur when a global climate model is started from a warm Southern Ocean state Over interannual to (short) multidecadal time scales, regional trends in Antarctic sea ice area are dominated by internal variability